THE EFFECTS OF THE IONOSPHERE ON GROUND-BASED DETECTION OF THE GLOBAL 21 cm SIGNAL FROM THE COSMIC DAWN AND THE DARK AGES - Datta, Abhirup; Bradley, Richard; Burns, Jack O.; Harker, Geraint; Komjathy, Attila; Lazio, T. Joseph W. (The Astrophysical journal, 2016)
ABSTRACT Detection of the global H i 21 cm signal from the Cosmic Dawn and the Epoch of Reionization is the key science driver for several ongoing ground-based and future ground-/space-based experiments. The crucial spectral features in the global 21 cm signal (turning points) occur at low radio frequencies . In addition to the human-generated radio frequency interference, Earth's ionosphere drastically corrupts low-frequency radio observations from the ground. In this paper, we examine the effects of time-varying ionospheric refraction, absorption, and thermal emission at these low radio frequencies and their combined effect on any ground-based global 21 cm experiment. It should be noted that this is the first study of the effect of a dynamic ionosphere on global 21 cm experiments. The fluctuations in the ionosphere are influenced by solar activity with flicker noise characteristics. The same characteristics are reflected in the ionospheric corruption to any radio signal passing through the ionosphere. As a result, any ground-based observations of the faint global 21 cm signal are corrupted by flicker noise (or noise, where f is the dynamical frequency) which scales as (where is the frequency of radio observation) in the presence of a bright galactic foreground ( , where s is the radio spectral index). Hence, the calibration of the ionosphere for any such experiment is critical. Any attempt to calibrate the ionospheric effects will be subject to the inaccuracies in the current ionospheric measurements using Global Positioning System (GPS) ionospheric measurements, riometer measurements, ionospheric soundings, etc. Even considering an optimistic improvement in the accuracy of GPS-total electron content measurements, we conclude that Earth's ionosphere poses a significant challenge in the absolute detection of the global 21 cm signal below 100 MHz.